Venetian Humanism in an Age of Patrician Dominance - King, Margaret L. (Book collections on Project MUSE., 2014)
In comprehensive detail Margaret King analyzes the activities of the patricians who were predominant in the ranks of the humanists and who made humanist thought a powerful tool in the service of their class and of the city itself. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback edition.